49 The basis of evidence-informed policymaking: communicating the potential impacts of policies. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Brick, Cameron; Freeman, Alexandra; Wooding, Steven; Skylark, William; Marteau, Theresa; Spiegelhalter, David
Abstract : Objectives: We call for a new research area on the effective communication of policy options to support evidence-informed policy making. It is critical to communicate the evidence of potential impacts of different policy options in such a way that individuals can understand them, and then apply their own values and goals in their policy decisions. There has been much research done on how to convey numbers and evidence for individual decisions about, for example, health or finances. In recent decades, communications providing options for individuals have increasingly moved towards showing both potential harms and benefits of options, using principles of clear communication that have been tested empirically. We set out to review communications around policy options – whether by governments, businesses or NGOs – to see whether the same principles were being, or could be, applied. Method: We carried out reviews of existing policy option communications from a wide range of domains and sources, of current guidelines for evidence summaries (such as governmental guidelines, and from organisations such as Cochrane), and of empirical studies of effectiveness of such communications in aiding comprehension. Results: We identified very little empirical evidence on how policy options are best communicated. However, we did identify some key challenges that we believe makes policy-level communication more complex than individual-level communication: Policies usually have heterogeneous effects across a population which a decision–maker will need to bear in mind (there are winners and losers). The need to display these differential effects in such a way to allow comparison adds complexity Policy outcomes are often measured across many different domains (eg. health, environmental, financial), each with different metrics Policies often have effects over long time periods, and these effects may be variable. The evidence for potential policy impacts often has very large uncertainties around it Although all of these apply to individual-level communication too, we believe that policy-level communication suffers even more greatly, and there is a bigger trade-off to be made between making communications comprehensive and comprehensible. Conclusions: In our review we identified examples of formats attempting to summarise policy-level evidence in an 'at a glance' summary. However, none of them appear to have been empirically tested on their target audiences. Equally, few organisational guidelines on how to present this kind of evidence cite any empirical research. We suggest that the field of policy-level communication is recognised as having a distinct set of challenges. We also suggest that empirical studies are called for in order to identify which lessons from individual-level communication research can be carried over, and how the specific challenges of policy-level communication are best met.